Physical geographical potentials for agriculture in Pomurje statistical region and changes in land use between 2000 and 2017 - Koltai, Tomaž (Journal for Geography, 2017)
The content of following the work analyses chosen physical-geographical indicators in Pomurje Statistical Region, which have proven to be great potentials for agriculture. Chosen indicators include functional inclination, exposition, pedological units, floor number and analysis of strategically important areas for cultivation and agriculture. The trends of exploitation of these potentials are demonstrated with observations of land use changes in the period between 2000 and 2017. The latter show occurring process of extensification, where lands in overgrowth, forests and build-up lands are expanding due to reduction of fields with gardens and vineyards. Most of these unfavourable processes occur in areas with most favourable condition for cultivation. This reflects negative trends and deviates from national paradigm in food self-sufficiency.